Persistent Primary Hyperparathyroidism, Severe Vitamin D Deficiency, and Multiple Pathological Fractures - Victoria Mendoza-Zubieta; Mauricio Carvallo-Venegas; Jorge Alberto Vargas-Castilla; Nicolás Ducoing-Sisto; Alfredo Alejandro Páramo-Lovera; Lourdes Josefina Balcázar-Hernández; Julián Malcolm Mac Gregor-Gooch (Case Reports in Endocrinology)
Persistent primary hyperparathyroidism (PHPT) refers to the sustained hypercalcemia state detected within the first six months following parathyroidectomy. When it coexists with severe vitamin D deficiency, the effects on bone can be devastating. We report the case of a 56-year-old woman who was sent to this center because of persistent hyperparathyroidism. Her disease had over 3 years of evolution with nephrolithiasis and hip fracture. Parathyroidectomy was performed in her local unit; however, she continued with hypercalcemia, bone pain, and pathological fractures. On admission, the patient was bedridden with multiple deformations by fractures in thoracic and pelvic members. Blood pressure was 100/80, heart rate was 86 per minute, and body mass index was 19 kg/m2. Calcium was 14 mg/dL, parathormone 1648 pg/mL, phosphorus 2.3 mg/dL, creatinine 2.4 mg/dL, urea 59 mg/dL, alkaline phosphatase 1580 U/L, and vitamin D 4 ng/mL. She received parenteral treatment of hypercalcemia and replenishment of vitamin D. The second surgical exploration was radioguided by gamma probe. A retroesophageal adenoma of 4 cm was resected. Conclusion. Persistent hyperparathyroidism with severe vitamin D deficiency can cause catastrophic skeletal bone softening and fractures.